(untitled) (Research, Society and Development, 2022)
The goal of this study is to evaluate eating behavior and strategies for Food and Nutrition Education strategies (FNE) for children with Autism Spectrum Disorder (ASD). The systematic review was developed in the following steps: elaboration of the scientific question, the search for evidence, review and selection of studies, methodological evaluation and presentation of results. In the search for data, 102 articles were pre-selected. In the sequence, those that didn’t match the inclusion criteria were excluded, 19 articles were fully analyzed, which shows that FNE is fundamental to improve autistic children’s eating behavior. FNE actions, with involvement of parents, caregivers and educators, in order to promote the adoption of healthy eating pattern, have proven to be more effective, once the involvement of all the people that are part of the person with ASD is essential for the success of nutritional interventions. The use of sensory familiarization methods for food, games and digital resources are approaches that are capable of causing changes in autistic children’s eating behavior. The traditional methodologies of FNE, like culinary workshops and lectures, are less effective, if compared to dynamic and interactive intervention practices.